Resistance of alkali-activated blast furnace slag to acids. Issue 1 (1st September 2022) - Hruby, P; Bilek, V; Topolar, L; Kalina, L; Iliushchenko, V; Koplik, J; Masilko, J; Soukal, F
Abstract : In this paper, the resistance of alkali-activated blast furnace slag to degradation processes caused by the action of various acids was studied. The ground granulated blast furnace slag was alkali-activated using sodium hydroxide in 6% Na2 O dosage by the slag weight and subjected to testing of acid resistance in both organic and inorganic acidic solutions (pH ≈ 3) for 84 days. Citric, acetic, hydrochloric, and sulphuric acids were used for these purposes. The reference samples were stored in water. The progress of degradation was studied using the phenolphthalein technique, compressive strength testing, and weight measurements. Moreover, the SEM-EDX was used for the characterization of the degradation processes and microstructure changes. The degradation of alkali-activated blast furnace slag occurred in both organic and inorganic acids; however, the action of organic acids appears to be much more deteriorating. The decrease in compressive strength of about 50% and 60% was observed for acetic and citric acid, while only of 32% and 23% in sulphuric and hydrochloric, respectively.